Self-perception of indoor air quality during sleep: preliminary findings from HypnosAir study - Araújo Gonçalves, Sara (2024)
Introduction: Building occupants' comfort and health have been enhanced by Indoor Air Quality (IAQ). This concept has drawn increased attention in recent decades from the international scientific community, political institutions, and environmental governance. Additionally, the traditional methods for assessing indoor air quality(IAQ)are intended to reduce and control indoor air pollutants without considering the individual perceptions of occupants. Therefore, it is important to have an integrated approach that incorporates both quantitative and qualitative methodologies. Furthermore, the HypnosAir study aims to investigate the environmental elements that influence sleep quality and assess the contribution that the sleeping environment plays in the daily integrated human exposure to air pollution.